Associations between ultrafine and fine particles and mortality in five central European cities — Results from the UFIREG study. (March 2016) - Lanzinger, Stefanie; Schneider, Alexandra; Breitner, Susanne; Stafoggia, Massimo; Erzen, Ivan; Dostal, Miroslav; Pastorkova, Anna; Bastian, Susanne; Cyrys, Josef; Zscheppang, Anja; Kolodnitska, Tetiana; Peters, Annette; et al.
Abstract: Background: Evidence on health effects of ultrafine particles (UFP) is still limited as they are usually not monitored routinely. The few epidemiological studies on UFP and (cause-specific) mortality so far have reported inconsistent results. Objectives: The main objective of the UFIREG project was to investigate the short-term associations between UFP and fine particulate matter (PM) < 2.5 μm (PM2.5 ) and daily (cause-specific) mortality in five European Cities. We also examined the effects of PM < 10 μm (PM10 ) and coarse particles (PM2.5–10 ). Methods: UFP (20–100 nm), PM and meteorological data were measured in Dresden and Augsburg (Germany), Prague (Czech Republic), Ljubljana (Slovenia) and Chernivtsi (Ukraine). Daily counts of natural and cardio-respiratory mortality were collected for all five cities. Depending on data availability, the following study periods were chosen: Augsburg and Dresden 2011–2012, Ljubljana and Prague 2012–2013, Chernivtsi 2013–March 2014. The associations between air pollutants and health outcomes were assessed using confounder-adjusted Poisson regression models examining single (lag 0–lag 5) and cumulative lags (lag 0–1, lag 2–5, and lag 0–5). City-specific estimates were pooled using meta-analyses methods. Results: Results indicated a delayed and prolonged association between UFP and respiratory mortality (9.9% [95%-confidence interval: − 6.3%; 28.8%] increase in association with a 6-day average increase of 2750 particles/cm 3 (average interquartile range across all cities)). Cardiovascular mortality increased by 3.0% [− 2.7%; 9.1%] and 4.1% [0.4%; 8.0%] in association with a 12.4 μg/m 3 and 4.7 μg/m 3 increase in the PM2.5 - and PM2.5–10 -averages of lag 2–5. Conclusions: We observed positive but not statistically significant associations between prolonged exposures to UFP and respiratory mortality, which were independent of particle mass exposures. Further multi-centre studies are needed investigating several years to produce more precise estimates on health effects of UFP. Highlights: We investigated the associations between ultrafine and fine particles and (cause-specific) mortality in multiple locations. The UFIREG study included cities from Central and Eastern European countries. Results indicated a delayed and prolonged association between ultrafine particles and respiratory mortality. PM2.5 and PM2.5–10 were associated with delayed increases in cardiovascular mortality.